1997
DOI: 10.1159/000111234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short- and Long-Term Withdrawal from Gestational Cocaine Treatment on Maternal Behavior and Aggression in Sprague-Dawley Rats

Abstract: Pregnant rats were treated with 30 mg/kg per day cocaine or normal saline either throughout gestation (GD 1–20, cocaine and saline withdrawal) or throughout gestation and continuing into lactation for 10 days postpartum (cocaine and saline nonwithdrawal). All cocaine-treated dams exhibited more disruptions in the onset of maternal behavior (retrieval, licking, crouching) and were more aggressive (threats and attacks) towards an intruder on postpartum day 6 than saline-treated dams. There were no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
5
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 18 publications
(28 reference statements)
5
47
5
2
Order By: Relevance
“…In animal models, gestational cocaine exposure leads to deficits in oxytocinergic activity, and to diminished maternal but increased aggressive behaviors, effects similar to those seen in dams treated centrally with an oxytocin antagonist rather than cocaine (Johns, Lubin et al, 1997;Johns, Noonan et al, 1997Lubin, Elliott et al, 2003). In the present investigation, mothers with gestational cocaine exposure reported more hostility and depressed mood, a trend towards more life stress over the past month, and less social support and sense of mastery and control in their lives.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In animal models, gestational cocaine exposure leads to deficits in oxytocinergic activity, and to diminished maternal but increased aggressive behaviors, effects similar to those seen in dams treated centrally with an oxytocin antagonist rather than cocaine (Johns, Lubin et al, 1997;Johns, Noonan et al, 1997Lubin, Elliott et al, 2003). In the present investigation, mothers with gestational cocaine exposure reported more hostility and depressed mood, a trend towards more life stress over the past month, and less social support and sense of mastery and control in their lives.…”
Section: Discussionsupporting
confidence: 66%
“…Specifically, rats given a moderate dose of cocaine either acutely during the postpartum period or chronically during pregnancy display increased maternal neglect of offspring (less feeding, licking, and nestbuilding) and either compulsive nonadaptive aggressive behavior (after chronic gestational treatment) or nonprotective behavior (after acute cocaine postpartum treatment) in the presence of an intruder Johns, Noonan, Zimmerman, Li, & Pedersen, 1994). Continuing exposure to postpartum cocaine may result in somewhat different patterns of disruptions in maternal behavior or aggression depending on dose and frequency of use during pregnancy (Johns, Lubin, Walker, Meter, & Mason, 1997;Johns, Noonan, Zimmerman, Li, & Pedersen, 1997;Johns et al, 2002;. These abnormal maternal behaviors appeared to be at least partially mediated by cocaine-induced changes in oxytocin activity (Elliott, Lubin, & Johns, 2001;Johns, Lubin et al, 1997;Lubin, Elliott, Black, & Johns, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cocaine (CC) treatment has been shown to increase MA significantly by PPD six (Johns et al 1994b) and under certain conditions PPD 10 (Heyser et al 1992), while acute treatment has been shown to decrease it (Johns et al 1994b;Vernotica et al 1996b;Johns et al 1998b). Importantly, the effects of CC do not result from cocaine withdrawal (Johns et al 1997b). Most findings to date are reported for lactating dams during the earlier postpartum period at more moderate doses of cocaine, with some data available for the later postpartum period at higher doses (Heyser et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine markedly impairs the expression of species-specific maternal behavior in postpartum rats when administered either systemically (Johns et al, 1994(Johns et al, , 1997(Johns et al, , 1998Kinsley et al, 1994;Vernotica et al, 1996a,b;Zimmerberg and Gray, 1992) or centrally into discrete central nervous system sites (Vernotica et al, 1999). We recently investigated the effects of cocaine as a pharmacological challenge to natural motivational processes in the lactating, postpartum rat, which is known to be highly motivated to seek and care for her offspring (Fahrbach and Pfaff, 1982;Fleming et al, 1994;Hauser and Gandelman, 1985;Lee et al, 2000;Magnusson and Fleming, 1995;Mattson et al, 2001Mattson et al, , 2003Wilsoncroft, 1969).…”
mentioning
confidence: 99%
“…We chose to study a dose of 10 mg/kg because we established that this dose is sufficient to impair the expression of maternal behavior when present in the blood (Vernotica et al, 1996a,b) and that this was a reinforcing dose for the late postpartum but not the early postpartum dam (Mattson et al, 2001;Wansaw et al, 2002Wansaw et al, , 2003a. Furthermore we used a subcutaneous route of administration because our group and others have used this approach in pregnant and postpartum females to avoid confounding influences on fetal development or nursing processes (Vernotica et al, 1996a,b;Mattson et al, 2001Mattson et al, , 2003Johns et al, 1997Johns et al, , 1998. Concentrations of cocaine and its two principal metabolites, BE and EME, were determined by liquid chromatography-tandem mass spectrometry in plasma collected up to 3 h after a subcutaneous cocaine injection; locomotor activity was measured in the same animals using automated activity monitors.…”
mentioning
confidence: 99%